A proportional decomposed fuzzy set-based AHP approach for LNG bunkering facility determination in maritime ports - Sahin, Gulsah; Akyuz, Emre; Cebi, Selcuk (TAYLOR & FRANCIS LTD, 2026)
Selecting liquefied natural gas (LNG) bunkering facilities is a complex multi-criteria decision-making (MCDM) challenge involving significant uncertainty. Decomposed Fuzzy Sets (DFS) manage this uncertainty by capturing decision-makers' cognitive processes through functional and dysfunctional questions. This article introduces proportionality-based models for DFS for the first time. By integrating the reciprocal questioning mechanism of DFS with proportion-based elicitation, the proposed framework captures expert assessments more precisely. A novel proportional decomposed fuzzy AHP method is developed and applied to the LNG bunkering facility selection problem in maritime ports. Findings demonstrate that safety considerations heavily dominate this process; specifically, fire and explosion risk and emergency response accessibility emerge as the most critical sub-criteria. Ultimately, this study confirms the necessity of a risk-oriented, regulation-compliant approach when planning LNG infrastructure in complex port environments.
Keywords: LNG bunkering facility; maritime decision-making; decomposed fuzzy sets; proportional fuzzy sets; multi-criteria decision-making; Analytic Hierarchy Process; Engineering